(untitled) (Cardiovascular Journal, 2019)
Background: This study was to compare the outcome of early versus delayed invasive intervention in acute coronary syndrome (ACS) patients. Methods: A total of 200 patients with ACS underwent early intervention group (d”24 h, n=100) and delayed intervention group (>24 to 72 h, n=100) after percutaneous coronary intervention (PCI) were enrolled. The probable outcomes were a composite of re-infarction, acute LVF, recurrent ischemia, repeat revascularization, bleeding, stroke or death at 30 days. Results: Male were predominating (74%vs26%). Left anterior descending artery was the commonest infarct related artery in both groups (p=0.114). Cardiac markers, Cardiogenic shock, Acute left ventricular failure (LVF) and ventilator requirement were significantly higher (p=0.007, p=0.060, p=0.009, p=0.002) and mean duration of hospital stay was longer (p <0.001) in delayed intervention group. At 30 days follow-up improvement of chest pain, LVF and ejection fraction were achieved significantly in patient undergoing early intervention (p <0.001, p=0.016, 54.7±7.4 vs. 48.4±6.9; p <0.001). Adverse outcome like acute LVF (7% vs. 21%; p=0.004), re-infarction (0% vs. 7%; p=0.007), acute kidney injury (AKI) (5% vs. 17%; p=0.007), bleeding (11% vs. 18%; p=0.160), stroke (3% vs. 9%; p=0.074), repeat revascularization (1% vs. 7%; p=0.032), death (0% vs. 5%; p=0.030) was higher in delayed invasive intervention group (p=0.001). Conclusion: Acute LVF, ventilator requirement and duration of hospital stay were significantly predominating in delayed intervention group. Early invasive strategy in ACS patient associated with lower rates of acute LVF, acute kidney injury, re-infarction, stroke, bleeding, repeat revascularization and death compared with delayed invasive strategy at 30 days of follow-up. Cardiovasc. j. 2019; 11(2): 129-138